Preparation of Bi2S3/carbon quantum dot hybrid materials with enhanced photocatalytic properties under ultraviolet-, visible- and near infrared-irradiation. Issue 41 (10th October 2017) - Wang, Jingmin; Zhang, Xiang; Wu, Ji; Chen, Hao; Sun, Song; Bao, Jun; Li, Shikuo; Bi, Hong
Abstract : Bi2 S3 /C-dot hybrid materials show an excellent UV-, vis- and NIR-photocatalytic behaviour for the degradation of MB or TC. Abstract : To solve the growing pollution issues, it is a promising alternative to develop efficient sunlight-driven photocatalysts for purifying organic wastewater. Herein, we report a new and efficient full-spectrum-responsive photocatalyst composed of Bi2 S3 nanotubes incorporated with carbon quantum dots (C-dots) for rapidly degrading methylene blue (MB) and tetracycline hydrochloride (TC). Compared with naked Bi2 S3 nanotubes, the as-prepared Bi2 S3 /C-dot nanohybrids show a remarkably higher photocatalytic efficiency for degrading MB or TC under ultraviolet (UV-), visible (vis-) and near-infrared (NIR-) light irradiation within 5 minutes. A possible mechanism is proposed for the enhanced photocatalytic activity of the Bi2 S3 /C-dot nanohybrids. A lower band gap as well as a wider absorbance in the UV-, vis- and NIR-regions can increase the light harvesting ability of the Bi2 S3 /C-dots. Meanwhile, the existence of C-dots can facilitate the charge separation of the photo-generated electron/hole pairs while electrons transfer from Bi2 S3 to C-dots. Besides, an increased surface area of the Bi2 S3 /C-dot nanohybrids also contributes to the excellent photocatalytic activity.